Liquid Crystalline Graphene Oxide/PEDOT:PSS Self-Assembled 3D Architecture for Binder-Free Supercapacitor Electrodes - Islam, Md. Monirul; Chidembo, Alfred T.; Aboutalebi, Seyed Hamed; Cardillo, Dean; Liu, Hua Kun; Konstantinov, Konstantin; Dou, Shi Xue (Frontiers in Energy Research, 2014)
Binder-free self-assembled 3D architecture electrodes have been fabricated by a novel convienient method. Liquid crystalline graphene oxide (LC GO) was used as precursor to interact with poly(3,4-ethylene-dioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) in dispersion in order to form a conductive polymer entrapped, self-assembled layer-by-layer structure. This advanced network containing PEDOT:PSS enabled us to ascribe the superior electrochemical properties of particular graphene sheets. This layer-by-layer self-assembled 3D architecture of best performing composite (rGO-PEDOT:PSS 25) showed excellent electrochemical performance of 434 F g-1 through chemical treatment. To highlight these advances, we further explored the practicality of the as-prepared electrode by varying the composite material content. An asymmetric supercapacitor device using aqueous electrolyte was also studied of this same composite. The resulting performance from this set up included a specific capacitance of 132 F g-1. Above all, we observed an increase in specific capacitance (19%) with increase in cycle life emphasizing the excellent stability of this device.